CO-PRODUCTION IN THE GOVERNANCE OF MARGOMULYO VILLAGE BASED ON LOCAL WISDOM (A CASE STUDY OF THE SAMIN COMMUNITY) - Asmorowati, Sulikah; Irianto, Jusuf; Reindrawati, Dian; Prasistya, Gabby Julia; Dwintania, Feny (Universitas Airlangga, 2024)
The village government is expected to be able to have a significant influence on development in various fields. However, this interest often hinders village governance implementation due to the insufficient institutional capacity of the village. This situation can have far-reaching effects on socio-economic issues within the community. Therefore, institutional capacity and the development of c0-production for village governments and communities are key elements in addressing issues in the village. In the governance management process, Margomulyo village officials still require development in various aspects, including governance knowledge and adopting information technology in bureaucracy. This community service activity provides training and mentoring to Margomulyo village government officials to enhance their capacity. The method employed in this activity involves delivering lectures, providing modules, and offering follow-up mentoring. The outcomes of this community service include an improvement in the knowledge of village officials regarding capacity building and co-production, as evidenced by post-test scores, as well as the enhancement of the village website and the prototype of the Saminku application.